KADAR KLOROFIL DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) SETELAH 2 TAHUN PENERAPAN BIOCHAR DAN PUPUK ORGANIK DI ENTISOL - Yohanes Manggas; Widowati Widowati; Hesti Triana Soelistiari (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[CHLOROPHYL CONCENTRATION AND YIELD OF PAKCOY (Brassica rapa L.) AFTER TWO YEARS OF BIOCHAR AND ORGANIC FERTILIZER APPLICATION IN ENTISOLS]. While nitrogen is necessary throughout the growth of vegetable plants, N deficiency disrupts chlorophyll formation, and hence, affecting the photosynthesis process. This study aimed to study the impact of the use of biochar and organic fertilizers on chlorophyll content and yield of Pak coy mustard in the third planting season in Entisols. This research was conducted in Bawang Hamlet, Tunggulwulung Village, Malang City. The first and second planting seasons, were May-November 2017 and August 2018-January 2019, respectively. Research on the third planting season was carried out in July-August 2019 without nitrogen fertilization. The research was arranged in a randomized block design, consisting of controls (Kl), chicken manure (A), compost (K), rice husk biochar (S), rice husk biochar + chicken manure (SA), rice husk biochar + compost (SK). The results showed that after two years of application, biochar and organic fertilizers had a positive impact on the increase in yield of Pakcoy even though fertilizer was not provided. The application of biochar and compost provided the best residual effect on the total chlorophyll of Pakcoy mustard.